2014
DOI: 10.1016/j.fishres.2013.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of artificial reefs: A case study of small scale fishers in Terengganu, Peninsular Malaysia

Abstract: This paper examines the economic benefits of artificial reefs (ARs) on artisanal fishers in Terengganu in the east coast of Peninsular Malaysia. The data for this study was obtained from interviews with 290 artisanal fishers from three districts of Terengganu, using a structured questionnaire. The study found that for fishers, income from fishing was significantly lower in AR areas, compared to non-AR areas. The income of the fishers who used drift nets as their main fishing gear was significantly lower in AR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Whitmarsh et al (2008) showed that in southern Portugal the fishing revenue from AR sites is 1.7 times of that from the control sites. On the contrary, Islam et al (2014) did not find benefits provided by concrete-based AR structures to the drift net users in Terengganu, Malaysia. Some studies have found that ARs can bolster local economy through ecotourism (Leeworthy et al, 2006;Kirkbride-Smith et al, 2013), but their ability to reduce pressure on the surrounding natural reefs may be limited (Oliveira et al, 2015).…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Whitmarsh et al (2008) showed that in southern Portugal the fishing revenue from AR sites is 1.7 times of that from the control sites. On the contrary, Islam et al (2014) did not find benefits provided by concrete-based AR structures to the drift net users in Terengganu, Malaysia. Some studies have found that ARs can bolster local economy through ecotourism (Leeworthy et al, 2006;Kirkbride-Smith et al, 2013), but their ability to reduce pressure on the surrounding natural reefs may be limited (Oliveira et al, 2015).…”
Section: Introductionmentioning
confidence: 72%
“…Japan has been one of the pioneers in fishing reef technology, aided by generous subsidy programs: during 1976-1987, Japanese government invested nearly $100 million annually to construct a total of 1.4 million m 3 of ARs (Grove et al, 1989). Over the years, ARs have been spreading to many parts of the world, including Southeast Asia (Islam et al, 2014), the Persian Gulf (Feary et al, 2011), North America (Thanner et al, 2006), Australia (Branden et al, 1994), and Europe (Santos and Monteiro, 1997;Jensen, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, three field surveys (Table 1) at six fishing landing centres in those states were taken as the research sites (Table 2). Fishing in Malaysian waters is generally conducted throughout the year, although fewer vessels operate during the monsoon season between November and January (Islam et al., 2014). In the ECPM during the post‐monsoon season, the catches are dominated by smaller fish groups (Isa et al., 1999), which might not reflect the actual catches.…”
Section: Methodsmentioning
confidence: 99%